Assessment of Skeletal Class I Subjects of Uttarakhand using Beta Angle - Rathod, Dhananjay; Rathod, GP; Rathod, Pankaj; Bisht, Gazal (Orthodontic Journal of Nepal, 2017)
Objective: To evaluate and establish the norms for Class I subjects of Uttarakhand population using the beta angle. Materials & Method: The sample included pre-treatment lateral cephalograms of 100 subjects aged 18-30 years belonging to Uttarakhand ethnicity and possessing skeletal Class I malocclusion with pleasing profile. Beta angle measurement was performed and compared with Caucasian standards. Result: No statistically significant difference was found in the beta angle values of Uttarakhand and Caucasian populations. Beta angle norms for Caucasian population can be applied for the Uttarakhand population. Conclusion: Beta angle is relatively a stable parameter in population with different ethnicities.